Keys to successful implementation of routine symptom monitoring in head and neck oncology with "Healthcare Monitor" and patients' perspectives of quality of care. Issue 12 (18th August 2020) - Dronkers, Emilie A. C.; Baatenburg de Jong, Robert J.; van der Poel, Egge F.; Sewnaik, Aniel; Offerman, Marinella P. J.
Abstract: Background: Value‐based health care is increasingly used to facilitate a systematic approach during follow‐up of patients. We developed Healthcare Monitor (HM): a structure of electronic patient‐reported outcome measures (ePROs) for the longitudinal follow‐up of head and neck cancer (HNC) patients. This study shares key lessons from implementation and seeks to provide insight into how patients experience HM. Methods: We conducted a mixed‐methods study using quantitative data from a nonrandomized retrospective survey of patients who received HM (n = 45) vs standard care (n = 46) and qualitative data from structured interviews (n = 15). Results: Implementation of HM included significant challenges. Finding common ground among clinicians, administrators, and IT staff was most important. Qualitative findings suggest that patients experienced better doctor‐patient communication and increased efficiency of the consultation using HM. Patients felt better prepared and experienced more focus on critical issues. Quantitative analysis did not show significant differences. Conclusions: Integration of HM into routine care for HNC patients may have increased patient‐centered care and facilitated screening of symptoms. However, future research is needed to analyze the potential benefits more extensively.